2008
DOI: 10.1007/s00049-007-0396-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential activity of non-fluorinated and fluorinated analogues of the European corn borer pheromone

Abstract: The differing antagonist activity of (Z)-13-hexadecen-2-one (Z11 -14 : MK, 1) and its 1,1,1-trifluoro derivative (Z11 -14 : TFMK, 2), two closely related analogues of the European corn borer pheromone Ostrinia nubilalis (Z strain), and their rationale is reported. Both chemicals exhibited some electrophysiological activity, and topical application of 10 pg of pheromone analogue on male antennae was sufficient to induce significantly lower depolarization responses to the pheromone versus untreated insects. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 51 publications
4
15
0
Order By: Relevance
“…A mixture of TFMKs 3 and 4 in the same ratio (96:4) as the corresponding components in the pheromone blend did not result in a significant difference in activity in comparison with the major analogue 3 alone. The present field results confirm the antagonist activity of other TFMK analogues of the pheromone that was previously recorded on S. nonagrioides ,16 O. nubilalis 40, 41 and Cydia pomonella (L.) 17. Moreover, in large‐scale field experiments, application of ( Z )‐11‐hexadecenyl trifluoromethyl ketone, an analogue of the S. nonagrioides pheromone, yielded a noticeable reduction in damage caused by this pest and by the sympatric species O. nubilalis , both in the number of plants attacked and in the number of larvae found per plant 42…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…A mixture of TFMKs 3 and 4 in the same ratio (96:4) as the corresponding components in the pheromone blend did not result in a significant difference in activity in comparison with the major analogue 3 alone. The present field results confirm the antagonist activity of other TFMK analogues of the pheromone that was previously recorded on S. nonagrioides ,16 O. nubilalis 40, 41 and Cydia pomonella (L.) 17. Moreover, in large‐scale field experiments, application of ( Z )‐11‐hexadecenyl trifluoromethyl ketone, an analogue of the S. nonagrioides pheromone, yielded a noticeable reduction in damage caused by this pest and by the sympatric species O. nubilalis , both in the number of plants attacked and in the number of larvae found per plant 42…”
Section: Resultssupporting
confidence: 91%
“…Pheromone inhibitors, as analogues of the natural pheromones, have been used in mating disruption experiments for pest control 43. The present authors have demonstrated in recent years that TFMKs are potent antagonists of the pheromone in the field and good inhibitors in electrophysiology and behaviour in the laboratory 16, 17, 38–42. In addition, although it has not been determined in antennal extracts of Z. pyrina , these chemicals displayed a remarkable antiesterase activity in S. littoralis ,11, 14 S. nonagrioides 44 and O. nubilalis.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Thus, TFMK analogs of the pheromones of S. nonagrioides and C. pomonella inhibit pheromone response at 1:1 pheromone : analog ratio (Bau et al, 1999;Giner et al, 2009), whereas for O. nubilalis the corresponding analog was active at the minimum ratio of 1:5 (Riba et al, 2005;Solé et al, 2008b). In the processionary moth T. pityocampa, a structural TFMK analog, in which the acetate group of the pheromone was replaced by the CH 2 COCF 3 group, a 5% blend with the pheromone decreased the close approach and source contact behaviour (Quero et al, 1995).…”
Section: Effect Of Pheromone Analogsmentioning
confidence: 97%
“…Thus, while some chemicals exert a remarkable inhibition of male behavioural responses to the pheromone in a wind tunnel, e.g. in Heliothis virescens (F.) (Albans et al, 1984) and O. nubilalis (Solé et al, 2008b), other reports indicate modest electrophysiological inhibitory activity, as in the turnip moth Agrotis segetum Denis & Schiffermüller (Liljefors et al, 1984). In the processionary moth, the MK analog blocked the electroantennogram (EAG) responses after pre-exposure of males to vapour of the chemical (Parrilla & Guerrero, 1994).…”
Section: Effect Of Pheromone Analogsmentioning
confidence: 99%